Motivation and Knowledge Transfer in Social Enterprises Management - Zbigniew ZONTEK; Ewa LIPIANIN-ZONTEK (Communications of International Proceedings, 2022)
This paper presents an empirical analysis of the motives and knowledge transfer aspects, researched qualitatively in Polish social enterprises. The paper uses current business theory to underpin an original research methodology, to expose knowledge, its management and transfer, in voluntary not-for-profit groups (communities of practice). The aim of the research was to identify the motivations, behavior and achievements of purposively selected individuals working in their community of practice. The results documents and evaluates many stories, obtained by qualitative semi-structured interview of individuals, all interviewed in the last few years, from groups from different sectors. The interviews were transcribed carefully, from digital audio recordings. The subsequent evaluation via interpretative phenomenological analysis (IPA), followed by other qualitative techniques allowed conclusions to be drawn and reported for each group and its individuals. The results demonstrated that similar processes of organizational learning and active knowledge transfer occurred in all the researched social enterprises. Developing the published methodologies, and applying them in this novel way to a very broad range of groups, contributes to the understanding of motivation, always altruistic in these cases. The analysis demonstrated what these disparate groups have in common, that they are all composed from altruistically motivated people, acquiring and transferring knowledge. Situated learning and active knowledge management occurred in all CoP’s. IPA showed that knowledge was transferred in and out, expertise from earlier experiences was applied, and transferred, becoming explicit. Knowledge management skills were applied in new contexts.
Keywords: Knowledge transfer; motivation; social enterprises management